Tranexamic Acid Treatment Decreases Hidden Blood Loss in Total Knee Arthroplasty. (November 2016) - Chen, Xin; Zhu, Xiongbai; Yang, Shengwu; Lin, Wenjun; Wang, Lu
Abstract : The aim of our meta-analysis is to investigate the effect of tranexamic acid (TXA) on hidden blood loss (HBL) in total knee arthroplasty (TKA). A literature search was undertaken to identify all cohort studies that investigated the effect of TXA on HBL in TKA. Both electronic database search and manual search were used to retrieve studies related to the topic, and the retrieved studies were screened according to our stringent inclusion and exclusion criteria. Comprehensive Meta-analysis 2.0 software (CMA 2.0) was used for statistical analysis of the data retrieved from selected case–cohort studies. A total of 480 studies were initially retrieved, and after further screening and selection, 7 studies were eventually incorporated into our meta-analysis. The 7 studies included a total of 530 osteoarthritis or rheumatic arthritis patients who had TKA, and among them, 250 patients received an intravenous injection of TXA as cases and 280 patients received an intravenous injection of sodium chloride as sterile placebo controls. Our meta-analysis revealed that the volume of HBL of cases was lower than that of controls, which was statistically significant. The ethnicity-stratified analysis suggested that the volume of HBL of cases was significantly lower than that of controls in both the Asians and whites, also at statistically significant levels. Our meta-analysis provides strong evidence that TXA significantly reduces HBL in TKA, thus TXA can be used as a standard drug to prevent/reduce HBL in TKA.